Assessing wound closure in mice using skin-punch biopsy - Mary B. Rowland; Patrick E. Moore; Chuong Bui; Robert N. Correll (STAR Protocols, 2023)
Summary: Defects in myofibroblast function may cause wound healing defects in a variety of tissue types. Here we describe a simple skin-punch biopsy approach to screen mouse models for defects in wound closure that does not require extensive surgical training or expensive equipment. Experimental results may serve as an initial proof of concept to determine whether further investigation is necessary or if defects in myofibroblast function observed in other systems also result in reduced skin wound healing. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.